Pemahaman Masyarakat dan Pengaruhnya gerhadap Penggunaan Produk Perbankan Syariah di Kota Jambi - Faturahman Faturahman (Banque Syar'i : Jurnal llmiah Perbankan Syariah, 2021)
The purpose of this study was to analyze the understanding of society and its influence on the use of Islamic banking products. The type of data used is primary data. Data collection was done by face to face interview using a questionnaire. The population in this study is the people of Jambi City. The sampling technique is done by multistage random sampling. Samples were taken at random as many as 200 respondents. The analysis technique uses descriptive analysis and simple regression analysis. The public's understanding in the City of Jambi towards Sharia Banking is seen the higher the level of public education, the higher the level of public understanding of Islamic banks, so that interest in the use of Islamic banking products is also increasing. There is a significant influence between people's understanding of the use of Islamic banking products in Jambi City.